Handbook of Micrometeorology A Guide for Surface Flux Measurement and Analysis - Lee, Xuhui; Massman, William; Law, Beverly; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
The Handbook of Micrometeorology is the most up-to-date reference for micrometeorological issues and methods related to the eddy covariance technique for estimating mass and energy exchange between the terrestrial biosphere and the atmosphere. It is intended to provide micrometeorologists, ecosystem scientists, boundary-layer meteorologists, and students involved in micrometeorology with the state of science on measurement and analysis. The Handbook is the culmination of many detailed discussions of theory, analysis, and practical applications by the leading scientists in the field. It provides useful advice for bringing coherence to estimates of mass and energy exchange for understanding the role of the terrestrial biosphere in global environmental change.
Averaging, Detrending, and Filtering of Eddy Covariance Time Series -- Coordinate Systems and Flux Bias Error -- Uncertainty in Eddy Covariance Flux Estimates Resulting from Spectral Attenuation -- Low Frequency Atmospheric Transport and Surface Flux Measurements -- Measurements of Trace Gas Fluxes in the Atmosphere Using Eddy Covariance: WPL Corrections Revisited -- Concerning the Measurement of Atmospheric Trace Gas Fluxes with Open- and Closed-Path Eddy Covariance System: The WPL Terms and Spectral Attenuation -- Stationarity, Homogeneity, and Ergodicity in Canopy Turbulence -- Post-Field Data Quality Control -- Advection and Modeling.
Keywords: METEOROLOGY; ENVIRONMENTAL SCIENCES; CLIMATIC CHANGES; PHYSICAL GEOGRAPHY; ENVIRONMENTAL PROTECTION; GEOSCIENCES; METEOROLOGY/CLIMATOLOGY.; ENVIRONMENT, GENERAL; ATMOSPHERIC PROTECTION/AIR QUALITY CONTROL/AIR POLLUTION; CLIMATE CHANGE; ENVIRONMENTAL PHYSICS; GEOSCIENCES, GENERAL